2010
DOI: 10.1242/jcs.067215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of STIM1 at ERK1/2 target sites modulates store-operated calcium entry

Abstract: SummaryStore-operated calcium entry (SOCE) is an important Ca 2+ entry pathway that regulates many cell functions. Upon store depletion, STIM1, a transmembrane protein located in the endoplasmic reticulum (ER), aggregates and relocates close to the plasma membrane (PM) where it activates store-operated calcium channels (SOCs). Although STIM1 was early defined as a phosphoprotein, the contribution of the phosphorylation has been elusive. In the present work, STIM1 was found to be a target of extracellular-signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
130
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 34 publications
12
130
0
Order By: Relevance
“…Together, our proteomics analysis identifies several putative substrates of PKCB such as MUNC18 (Brochetta et al , 2014; Genc et al , 2014), SNAP23 (Polgár et al , 2003; Lorentz et al , 2012), STIM1 (Pozo‐Guisado et al , 2010), and MYH9 (Ludowyke et al , 2006) (Appendix Table S1) that may enhance mast cell secretion as a positive arm in the incoherent feed‐forward regulation (Fig 4F). Surprisingly, we also discovered that VAMP8 has an evolutionarily conserved phosphorylation motif in the center of the SNARE fusion complex that acts in parallel as a negative regulatory arm in the same circuit to prevent fusion (Fig 4G).…”
Section: Discussionmentioning
confidence: 87%
“…Together, our proteomics analysis identifies several putative substrates of PKCB such as MUNC18 (Brochetta et al , 2014; Genc et al , 2014), SNAP23 (Polgár et al , 2003; Lorentz et al , 2012), STIM1 (Pozo‐Guisado et al , 2010), and MYH9 (Ludowyke et al , 2006) (Appendix Table S1) that may enhance mast cell secretion as a positive arm in the incoherent feed‐forward regulation (Fig 4F). Surprisingly, we also discovered that VAMP8 has an evolutionarily conserved phosphorylation motif in the center of the SNARE fusion complex that acts in parallel as a negative regulatory arm in the same circuit to prevent fusion (Fig 4G).…”
Section: Discussionmentioning
confidence: 87%
“…is required for thapsigargin-induced activation of SOCE by enhancing STIM1-Orai1 coupling (92). In neonatal cardiomyocytes we have shown that activation of SOCE by thapsigargin also increases STIM1 phosphorylation (153).…”
mentioning
confidence: 71%
“…The K domain is predicted to contain a flexible central amphipathic ␣-helix that is flanked by globular positively charged regions in a dumbbell-like structure (148). The region between the ID and K domains appears to be the major regulatory region and contains most of the currently identified phosphorylation sites (62,92,109,143). Although it is now well recognized that STIM1 is a phosphoprotein (31,62), the molecular pathways responsible for controlling STIM1 phosphorylation are not well defined and the physiological function of many of the phosphorylation sites remain to be identified.…”
mentioning
confidence: 99%
“…Several mechanisms that affect the magnitude of SOCE have been identified, such as transcriptional regulation , posttranslational modifications Hawkins et al, 2010;Pozo-Guisado et al, 2010), and accessory proteins Store-operated calcium entry (SOCE) regulates a wide variety of essential cellular functions. SOCE is mediated by STIM1 and STIM2, which sense depletion of ER Ca 2+ stores and activate Orai channels in the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%